Onyshchenko V.A. Forests of order Fagetalia sylvaticae in Ukraine - Ситник, К.М. (Український ботанічний журнал, 2010)
Рецензія на книгу: Onyshchenko V.A. Forests of order Fagetalia sylvaticae in Ukraine / Ed.: S.L. Mosyakin. — Kyiv: Alterpress, 2009. — 212 p.